Privatization, financial development, property rights and growth - Marcelin, Isaac; Mathur, Ike (Journal of Banking & Finance, 2015)
This study analyzes how prevailing institutional arrangements i.e., property rights, contracting rights, political institutions, and corporate governance practices affect privatized firms’ performance, capital markets development, and economic growth. Most of the studies surveyed show that privatization enhances privatized firms performance, efficiency, and profitability, which percolates to economic growth. Privatized firms performed better in countries with better regulatory and legal frameworks. Partial privatization may be beneficial in countries with weak institutions, namely, the French civil law countries. The stronger the economic and the governing institutions, the easier it is for privatized firms to thrive and contribute to economic growth. Overall, privatization allows firms to achieve improved efficiency while driving the development of the financial sector.